Supplementary techniques for pain control during root canal treatment of lower posterior teeth with irreversible pulpitis: A systematic review and meta-analysis - Tupyota P. (2017)
© 2017 Australian Society of Endodontology Inc. The purpose of this systematic review and meta-analysis was to evaluate utilisation of supplementary techniques for pain control during root canal treatment of lower molars with irreversible pulpitis. The literature was searched using electronic databases up to year 2012. Seventeen studies with 1504 participants were included and each study compared experimental interventions with a standard treatment, i.e. the inferior alveolar nerve block. Changing the injection techniques or supplemental injection had no significant effect on pulp anaesthesia compared to the standard treatment (P = 1.00 or P = 0.14), whereas changing anaesthetic features and increasing anaesthetic volumes resulted in significantly higher rates of anaesthesia than those of the standard treatment (P = 0.03 and P = 0.007, respectively). Premedication with non-steroidal anti-inflammatory drugs (NSAIDs) also significantly increased the success rate of anaesthesia (P = 0.001). Taken together, increased anaesthetic volumes and premedication with NSAIDs provide predictable anaesthesia and more pain control during endodontic treatment of lower molars with irreversible pulpitis.